Interaksi Antara Pendidik Dengan Peserta Didik Dan Pembentukkan Karakter Alumni Yang Sukses - FERDINAL R; ELVINA SANDRA (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT There are many problem in learning process, which one is the interaction between educators and learners and establishment of succesful the character of the graduated. The interaction between educators and learners is very important in learning process, the learners must be understanding of the educators message in the process of the learning. In the other word, interaction as instructors earn them respect, admiration, and popolarity. It also true because without the interaction impossible the learning process will becoming accomplished . Establishment of a successful way of the graduates characters just things that important also in the education process. Because this is a goal of the learning process and the enhancement of the education greet today. Thre are three key of getting the succesful in establishment of the graduates characters, skills, knowledge, and the attitude of character and also the mindset. Furthermore, Interaction is the complete that the educators and learners have to apply in the process of eduation or learning process and the way to establishment of the characters building of the graduation or learners. Keyword : education, educators and learners, character of the graduated, mindset.